Time-reversal imaging for concrete hole defect based on implantable sensing technology. (1st March 2023) - Yang, Ziqian; Chen, Qingjun; Zhang, Minghui; Yuan, Cheng; Kong, Qingzhao
Abstract: Time-reversal imaging algorithm based on subspace theory has been verified as an efficient technique for localization of targets and damages in aerospace field. However, it is still a challenge to apply this technique for damage imaging of civil structures due to multi-phase concrete material and the interference of noises. To close the gap, this study proposes a novel subspace-based time-reversal imaging (STRI) algorithm enabled by implantable sensing technology. The STRI algorithm constructs a special three-dimensional transfer matrix and decomposes the time-reversal operator (TRO) into a certain frequency band. The eigenvectors corresponding to the noise subspace are used to reconstruct the imaging map. A novel transducer named cylindrical concrete implantable module (CCIM) is developed to install on the host structure for sending and receiving probe signals; its basic layout and fabrication are introduced in detail. Both the numerical and experimental studies validate the performance of the CCIM and STRI algorithm for hole damage imaging in concrete. Results show that the STRI algorithm overcomes the impacts of noises, offering a higher accuracy of damage areas compared to conventional algorithm. The proposed STRI algorithm enabled by implantable sensing technology has potential applications for real structural hole damage profiling and condition assessment.